Breastfeeding linked to the reduction of both rotavirus shedding and IgA levels after Rotarix® immunization in Mexican infants. Issue 44 (17th October 2016) - Bautista-Marquez, Aurora; Velasquez, Daniel E.; Esparza-Aguilar, Marcelino; Luna-Cruz, Maria; Ruiz-Moran, Tatiana; Sugata, Ken; Jiang, Baoming; Parashar, Umesh; Patel, Manish; Richardson, Vesta
Abstract: We examined potential risk factors on vaccine virus shedding and antibody seroresponse to human rotavirus vaccine (Rotarix) in Mexican infants. Two doses of Rotarix were administered to infants during the first two visits for their routine childhood immunization (∼8 and 15 weeks of age) in Mexico City. Infant's characteristics and socioeconomic indicators were obtained, including history of long-term feeding practices (exclusively/predominantly breastfed and exclusively/predominantly non-breastfed). Two serum specimens were collected, one during the second rotavirus vaccine visit and one 7 weeks later. Stool specimens were collected between days 4–7 after each of the two rotavirus vaccine doses. Rotavirus IgA and IgG titers in serum were determined by enzyme immunoassays (EIA) and rotavirus shedding in stool was assessed by EIA and confirmed by RT-PCR. The overall rotavirus IgA geometric mean titers (GMT) increased significantly post dose 2 from post dose 1 [176 (95%CI: 113–273) to 335 (238–471); p = 0.020). Infants who were exclusively/predominantly breastfed were less likely to shed vaccine virus in stool than those who were formula-fed (22% vs. 43%, p = 0.016). Infants who were breastfed had lower rotavirus IgA titers than those who were formula-fed after dose 1 [GMT: 145 (84–250) vs. 267 (126–566) p = 0.188] and dose 2 [236 (147–378) vs.578 (367–910), p = 0.007]. Infants who shed vaccine virus post dose 1 had significantly higher serum IgA GMT than those who did not shed [425 (188–965) vs. 150 (84–266), p = 0.038]. Breastfeeding was linked with the reduction of both stool vaccine shedding, and IgA seroresponse. The reduced rotavirus replication in the gut and shedding after dose 1 may explain in part the lower IgA response in serum.